PHYSIOLOGICAL AND BIOCHEMICAL EFFECTS OF POLYETHYLENE GLYCOL (PEG) INDUCED DROUGHT STRESS CONDITION IN FOUR VARIETIES OF INDIAN TOMATOES (LYCOPERSICON ESCULENTUM). - V.D.MENDHULKAR; K NISHA (International Journal of Pharma and Bio Sciences, 2015)
The present work deals with the study of Poly ethylene glycol (6000) induced drought stress condition and analysis of its physio-biochemical effects in 4 genotypes of Indian tomato (Lycopersicon esculentum).The genotypes, Deep-953, cultivar 327, 326and Aditya-955 were treated with 15% poly ethylene glycol. The parameters like rate of germination, relative water content, leaf area, days of maturity, osmolite content and content of photosynthetic pigments were analysed. The significant reduction in seed germination was as low as 60% in Deep-953, 40% in cultivar 327, 10% in cultivar 326 and 40% inAditya-955.The reduced leaf area, tissue water content and change in physiological characteristics in stress sensitive plants Deep-953, cultivar 327 and Aditya-955.Analysis of variance showed significant difference (P<0.05) in the mean proline content in tomato varieties subjected to stress. Result indicates treatment dependent variations in proline content. However, the tomato cultivar 326 was able to express best tolerance to induced drought.